Integrasi Faktor Struktur dan Domestik dalam Kebijakan Jaringan Bersih 5G Amerika Serikat pada Masa Pemerintahan Donald Trump - Advenia Prihatini Widyaningrum; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The development of 5G technology has become a new realm in the technological competition between the United States and China. This technology competition focuses on competing for dominance of global core technologies, which can provide economic benefits through standard setting, patents, and global supply chains. Huawei, a technology company from China, is said to have dominated 5G development based on the number of patents and company spending on research and development of this internet network. The United States as a first-mover country that for decades has led the development of global internet network technology, is facing challenges with Huawei's rapid development in the development of 5G technology. The escalation of competition has increased with the designation of Huawei as a threat to the United States by President Donald Trump. The Clean Network policy initiative was also later issued by the Trump administration to block Huawei's 5G network in America. This initiative was also used to lobby allied countries to join this policy. This raises questions about the factors driving the establishment of the Clean Network policy as a response to United States' concerns about the leadership of Chinese tech companies in 5G development. This research uses Neoclassical Realism theory to explain the factors causing the choice of the Clean Network policy as the United States' response to pressure from the leadership of Chinese companies. This theory will combine the analysis of international and domestic structures in understanding the behavior of the United States.